Civic Education for Lower Secondary Students - Jurs, Pāvels; Samuseviča, Alīda (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
Nowadays the question of the necessity for the civic upbringing in the general curriculum in the system of education of Latvia has been raised. At the same time students` knowledge as well as skills and attitude of civic education have not been fully analyzed. Before carrying out the particular reforms in the content of education, we must assess the situation and find a balanced, purposeful and theoretically reasonable holistic systemic approach for promotion of the citizenship. Through using theoretical and empirical research methods, the process of researching is characterized and the data that reflects students' civic knowledge, skills, attitude and values has been analyzed. This publication contains systematized conclusions that outline the possibilities for pedagogical activities that promote civic competence for students in the general education institutions.